Narrative Review: Peluang dan Tantangan Green Sukuk di Indonesia - Pujiantoro, Aisya Sekar Gading; Dindalila, Deariztria; Fakhruddin, Naufal (Diponegoro Journal of Islamic Economics and Business, 2021)
Indonesia as a tropical country is considered as one of the richest countries in the world with its biodiversity. However, this condition will make Indonesia more vunerable to climate change. Therefore, one of government’s commitment in respond to the climate change is by initiating various green finaning instrumentswhere one of which is geen sukuk. Green sukuk is one instrument that relevant to overcome climate change as this type of financing is specifically targeted development with considering environmental aspect. This study aims to examin opportunities and challanges in developing green sukuk financing in Indonesia. By using narrative review from many sources, the result indicates that there are opportunities for Indonesia to develop green sukuk. Several reasons are  the existence of islamic financial market that still growing from time to time, investor awareness of environment issues, and demand for energy supply, In addition there are several challange for Indonesia to develop green sukuk instrument such as low public literacy related to green sukuk, lack of socialization, and several characteristics of investors.